Implant-supported overdenture, an alternative option for the rehabilitation of a completely edentulous mandibular arch - Ganesh Ram Kumar Rajapandi; Ahila Singaravel Chidambaranathan; Muthukumar Balasubramaniam (Journal of Oral Research and Review)
Edentulism has been a long-standing concern in prosthodontics. Several of the drawbacks of conventional denture therapy have been observed to be addressed by implant therapy nowadays. A 55-year-old female came with the chief complaint of missing teeth related to the mandible. This report aims to give insight into a case of a mandibular edentulous patient, who was treated with the help of an implant retained overdenture in the mandibular arch. Two implants were placed with the aid of the cone-beam computed tomography report. After 4 months, the prosthetic phase began with the placement of the healing abutment, and an open tray impression was made followed by a jaw relation. A bar framework was fabricated followed by a wax trial, and denture insertion was done. Overdentures are a good option for severely resorbed edentulous jaws. For the edentulous mandibular arch, implant-supported overdentures are the preferred course of treatment due to their prosthesis survival rate (>97%) and low prosthetic complications.